Intriguing light-emission features of ketoprofen-based Eu(III) adduct due to a strong electron-phonon coupling - Lahoud, M. G. [UNESP]; Frem, R. C.G. [UNESP]; Gálico, D. A.; Bannach, G.; Nolasco, M. M.; Ferreira, R. A.S.; Carlos, L. D. (Elsevier, 2016)
Lanthanide-based coordination compounds of molecular formula [Ln(keto)3(H2O)], where Ln=Gd, Eu and keto=ketoprofen, were synthesized and their photoluminescence features were detailed in the 12-300 K interval. The emission spectra of [Eu(keto)3(H2O)] reveal a strong dependence with the temperature, well-illustrated by an unusual large blue-shift (∼17 cm-1) of the 5D0→7F0 transition as the temperature is raised. The arithmetic difference between the absorption spectrum of [Eu(keto)3(H2O)] with that of [Gd(keto)3(H2O)] pointed out the presence of a ligand-to-metal charge transfer (LMCT) band (320-370 nm). From the [Gd(keto)3(H2O)] phosphorescence the energy of the keto-related triplet states was determined showing a large overlap with the intra-4f6 levels and a strong electron-phonon coupling. The high-resonance between the LMCT and triplet states and the Eu3+ levels leads to a strong dependence of the 5D0 lifetime value, typical of the presence of operative energy transfer processes.
Keywords: 5D0 lifetime dependence with the excitation wavelength; Electron-phonon coupling; Ketoprofen; Lanthanide coordination compounds